The Mediation Role of the Village Fund Management System on the Relationship Between HR Advantages, Utilization of IT, and Village Government Performance - Lukiastuti, Fitri; Iskanto; Djou, LD Gadi (Research and Development Agency Ministry of Home Affairs, 2022)
The enactment of Law No. 6 of 2014 concerning Villages carries the views and new concepts of village governance policies nationally. The Village Law provides a good opportunity for villages to manage their administration and development to improve rural residents' welfare and quality of life. This research investigates the influence of HR advantages and IT utilization on village fund management system and village government performance and the influence of HR advantages and IT utilization on village government performance mediated by village fund management system. Respondents were 287 village officials in Tegal Regency. Data collection method using simple random sampling. The data analysis used is SEM-PLS analysis. The findings show that HR advantages do not influence the village fund management system, and IT utilization influences it. HR advantages influence village government performance, and IT utilization does not influence village government performance. Village fund management systems influence village government performance. The village fund management system cannot mediate the relationship between HR advantages and village government performance but can mediate the relationship between HR advantages and village government performance. The village government can implement the results of this study to effectively improve some policies related to HR advantages and IT utilization.